All the science that is fit to blog: An analysis of science blogging practices - Jarreau, Paige (New Zealand Science Review, 2015)
​This PhD dissertation examines science blogging practices, including motivations, routines and content decision rules, across a wide range of science bloggers. Previous research has largely failed to investigate science blog-ging practices from science bloggers’ perspective or to establish a sociological framework for understanding how science bloggers decide what to blog about. I address this gap in previous research by conducting qualitative in-depth interviews with 50 science bloggers and an extensive survey of blogging motivations, approaches, content decisions rules, values and editorial constraints for over 600 active science bloggers. Results reveal that science blog content is shaped heavily by not only individual factors including personal interest, but also a variety of social forces at levels of routines, organisations or blogging communities, and social institutions. Factors revealed herein to shape science blog content are placed into a sociological framework, an adapted version of Shoemaker and Reese’s (1996) Hierarchical Model of Influences, in order to guide current and future research on the sociology of science blogging. Shoemaker and Reese’s Hierarchical Model of Influences is a model of the factors that influence mass media content, which has been used previously by mass communi-cation researchers to guide analysis of mass media content production. In the visual model, concentric circles represent relative hierarchical levels of influences on media content, starting an individuals and expanding out to routines, organisations, extra-media influences and ideology. I adapt this model based on the factors found herein to influence science blog content, such as bloggers’ individual motivations, editorial constraints, and access to information sources.